2018
DOI: 10.12968/bjon.2018.27.21.1246
|View full text |Cite
|
Sign up to set email alerts
|

Self-confidence and attitude of acute care nurses to the presence of family members during resuscitation

Abstract: Aim: the present study aimed to assess the relationship between attitude to the presence of family members during cardiopulmonary resuscitation and confidence of acute care nurses in performing cardiopulmonary resuscitation in the presence of family. Methods: this descriptive-analytical study was conducted on nurses working in acute care units (intensive care unit, coronary care unit, and emergency department) in Iran in 2017. A total of 150 nurses entered the study by convenience sampling. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
2
12
0
1
Order By: Relevance
“…Also, this study revealed that those who got professional training in dealing with COVID-19 patients had a higher level of professional self-concept than those who did not get such training. This result is consistent with other studies [24,25,35,39,40]. These studies agreed that the trained nurses have higher professional self-confidence than those who did not get such training.…”
Section: Deference Based On the Work-related Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…Also, this study revealed that those who got professional training in dealing with COVID-19 patients had a higher level of professional self-concept than those who did not get such training. This result is consistent with other studies [24,25,35,39,40]. These studies agreed that the trained nurses have higher professional self-confidence than those who did not get such training.…”
Section: Deference Based On the Work-related Factorssupporting
confidence: 92%
“…According to Tivener and Gloe (2015), placing nursing students in a crisis situation like a high-fidelity simulation for cardiopulmonary resuscitation (CPR) and exposing them to such an experience increased the nurses' student self-confidence [24]. Moreover, nurses with higher professional self-confidence had more positive behaviors toward family members' presence during a CPR code [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies both in hospitals (Rafiei et al, 2018) and out of hospitals (Bremer et al, 2012) have shown the complexity of caring in this context, both during the event of resucitation and when caring for bereaved family members. Uneasiness and short-comings have been described as barriers by healthcare professionals, for example, a lack of courage to face different reactions among family members and one's own vulnerability (Bremer et al, 2012;Rafiei et al, 2018). Walker and Deacon (2016) also show that caring for the suddenly bereaved is experienced as a source of tension and unease by healthcare professionals.…”
Section: Comprehensive Understanding and Reflectionsmentioning
confidence: 99%
“…The majority of the participants who had higher levels of education and had undertaken a training program on family-centered care stated that they felt in control and more skilled at their work [ 13 ]. A few studies have explained the attitudes of nurses and nursing students toward the involvement of family in the context of daily care and CPR [ 14 , 15 ]. In addition, previous research has focused primarily on limited aspects and have not paid heed to family participation in hospital settings [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have explained the attitudes of nurses and nursing students toward the involvement of family in the context of daily care and CPR [ 14 , 15 ]. In addition, previous research has focused primarily on limited aspects and have not paid heed to family participation in hospital settings [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The current study aimed to describe nurses’ and nursing students’ perceptions of family involvement in the care of hospitalized adult patients.…”
Section: Introductionmentioning
confidence: 99%